Formação continuada de professores alfabetizadores na perspectiva da práxis discursiva - Arnone, Kathiuscia Rosane Araújo (2022)
This study develops a theme around the formation of literacy teachers from the perspective of emancipatory discursive praxis. It seeks to understand how a process of training literacy teachers is constituted from the perspective of emancipatory praxis, taking the concrete reality of these teachers and students as a reference for the teaching-learning process. It uses the methodological theoretical contributions based on the enunciative theory of language and the presuppositions of the categories of analysis of the dialectical historical materialist method. It used instruments such as questionnaires, conversation and dialogue circles. The present training is identified with the emancipatory popular project in opposition to the hegemonic neoliberal project proposed by the current policy of teacher training. The results showed that it is possible to develop a proposal for continuing education at school that gives teachers back their place of control over the way of production of their creative pedagogical work.